Online Model For Translation Teaching And Learning Pasca Covid-19 Pandemic For EFL University Learners - Sujarwo, Sujarwo; Sukmawati, Sukmawati; Asdar, Asdar; Marzuki, Mutmainnah; Jubhari, Yuriatson; Enjelina Debibillian, Maria (Universitas Cokroaminoto Palopo, 2024)
This study aimed to provide more information about online model for translation teaching and learning pasca covid-19 pandemic for EFL university learners. This study utilised qualitative descriptive methodology, namely through conducting a survey, to conduct an empirical examination on a specific issue in the field of translation. The survey was administered to a group of students, providing useful information. A total of 16 students were selected as a sample from the English education department of Universitas Megarezky. The findings indicated that the online translation course was successful for students in using some online media (Free Online Translator and Google Classroom.). Based on documented field observations, translation lecturer utilized Google Classroom as online learning tools to oversee theoretical tasks, facilitate material discussions, and employed Free Online Translator for translation practice. Most students possess the necessary information and abilities to effectively utilise and benefit from the website. According to the lecturer's teaching technique, few of the respondents expressed their dislike for the online lecture mode due to the challenges they encountered. It can be concluded that most of respondents has a favorable opinion of using Free Online Translator and Google Classroom. This has the potential to be a beneficial enhancement for approaching online lectures in the future study